(untitled) (Indian Journal of Animal Production and Management, 2025)
The aim of the present study was to evaluate the effect of two commercial diets on the production performance of broiler chicks under tropical conditions. The experiment was conducted with 100 two-day-old Cobb-500TM chicks randomly assigned to two treatments, each group using two levels of a commercial crumb feed brand (n=50): Group 1 Apiaba® commercial feed (23% and 18.5% protein) and Group 2 Purina® commercial feed (23% and 18.5% protein). No significant differences were found between treatments for any of the production variables evaluated (P > 0.05). However, there was a statistical trend for initial weight (P = 0.06). Regarding feed intake, broilers fed Apiaba® had higher feed intake in weeks four and five compared to Purina® (13.04% week 4 and 9.08% week 5, P < 0.05). These results indicate that the differences in intake occurred during the mid-growth stages, while no significant differences were observed during the other weeks. In general, both diets gave similar results under the conditions evaluated, making them reliable alternatives for small scale poultry farmers under conditions similar to those of the present study.